The Effect of Hedonic Shopping Motivation and Fashion Involvement on Impulse Buying Behavior of Fashion Products at Shopee - Katerina, Angel; Simanjuntak, Anisa (Universitas Pamulang, 2024)
This study aims to determine the effect of hedonic shopping motivation and fashion involvement on impulse buying behavior on fashion products at Shopee. The data used in this study are primary data. The population in this study were Shopee e-commerce consumers. The sample used was 106 respondents. The sampling technique is non-probability sampling and purposive sampling method. Primary data in this study were obtained from a questionnaire. The data analysis techniques used are validity test, reliability test, classical assumption test consisting of normality test, multicolonierity test, and heteroscedasticity test, multiple linear regression analysis, hypothesis testing consisting of t test, f test and coefficient of determination. The results in this study indicate that partially hedonic shopping motivation has no significant effect on impulse buying behavior while fashion involvement has a positive and significant effect on impulse buying behavior. Simultaneously, hedonic shopping motivation and fashion involvement affect the impulse buying behavior of fashion products at Shopee.